Near-hanging Injury in a Pediatric Patient - Espinoza-Espinoza, Yudit (2022)
Suicide is a public health problem. Suicide by hanging is seen in all ages, starting around the age of 10-12. "Hanging injuries" is the term used to refer to people who survive after hanging. We present the case of a pediatric patient who survived mechanical asphyxia by hanging. A 12-year-old female patient who recently attempted suicide by hanging herself was admitted to the nearest hospital presenting "near-hanging injuries." She received ventilatory support and sedation-analgesia in the Pediatric Intensive Care Unit (PICU), treating cerebral edema with mannitol. Upon discharge, she presented neurological and structural sequelae. Although suicide is one of the most common causes of death in the pediatric population, near-hanging injuries are rare in this setting. Patients with these injuries should be treated aggressively and early to avoid possible complications. In this case, the family's action and the late treatment influenced the lousy evolution of the patient.